2022
DOI: 10.1111/dme.14912
|View full text |Cite
|
Sign up to set email alerts
|

Banting memorial lecture 2022: ‘Type 2 diabetes and nonalcoholic fatty liver disease: Partners in crime’

Abstract: Nonalcoholic fatty liver disease (NAFLD) was first described in the 1980s, but in the 21st century, NAFLD has become a very common condition. The explanation for this relatively recent problem is in large part due to the recent epidemic of obesity and type 2 diabetes (T2DM) increasing the risk of NAFLD. NAFLD is a silent condition that may not become manifest until severe liver damage (fibrosis or cirrhosis) has occurred. Consequently, NAFLD and its complications often remain undiagnosed. Research evidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…It is important to note that NAFLD and T2D form part of a vicious spiral of worsening diseases, where one condition affects the other and vice versa. 46 Given that diabetes markedly increases the risk of liver fibrosis, 46,47 or liver biopsy to identify fatty liver. However, liver biopsy is neither feasible nor ethical for healthy participants, and imaging modalities such as computed tomography or magnetic resonance imaging are not practical or cost-effective for routine healthcare check-ups in this large population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that NAFLD and T2D form part of a vicious spiral of worsening diseases, where one condition affects the other and vice versa. 46 Given that diabetes markedly increases the risk of liver fibrosis, 46,47 or liver biopsy to identify fatty liver. However, liver biopsy is neither feasible nor ethical for healthy participants, and imaging modalities such as computed tomography or magnetic resonance imaging are not practical or cost-effective for routine healthcare check-ups in this large population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we excluded all who had diabetes at the study baseline. It is important to note that NAFLD and T2D form part of a vicious spiral of worsening diseases, where one condition affects the other and vice versa 46 . Given that diabetes markedly increases the risk of liver fibrosis, 46,47 excluding individuals with T2D to define the diabetes‐free at baseline might result in specific selection of those with fibrosis but not related to T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Worryingly, the global prevalence of NAFLD is expected to increase dramatically in the near future, in parallel with the increasing rates of obesity and T2DM globally [ 1 ]. T2DM and NAFLD represent a “vicious circle”, whereby the presence of one condition adversely affects the other and vice versa [ 3 ]. Compared with subjects without T2DM, patients with T2DM are more likely to have or develop the more advanced forms of NAFLD, such as nonalcoholic steatohepatitis (NASH), advanced fibrosis or cirrhosis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, overwhelming evidence has shown that nonalcoholic fatty liver disease (NAFLD) is a multisystem disease and is a risk factor for other extrahepatic diseases that require a holistic approach to treatment [2,3] . In support of that argument, there is now evidence that NAFLD is an independent risk factor for T2DM [4] , cardiovascular disease (CVD) [5] , chronic kidney disease [6] , congestive heart failure [7] , and certain extrahepatic cancers (principally gastrointestinal cancers, breast cancers, and gynecological cancers) [8] . Many of these extrahepatic diseases share common cardiometabolic risk factors, such as central obesity, hypertension, glucose intolerance, insulin resistance and atherogenic dyslipidemia, and it has been known for several years that many of these cardiometabolic risk factors tend to cluster together in affected patients at risk of these extrahepatic disease complications [2,9] .…”
mentioning
confidence: 99%